The Relationship of Intergenerational Perceptions of Work Ethics and Workplace Deviation Behaviors in Academic Staff - Eda Sultan Arar; Serap Şahin (Journal of Information and Organizational Sciences, 2022)
The aim of the research is to examine the work ethics perceptions of academics from different generations and the relationship between these perceptions and workplace deviation behaviors. In line with the purpose, the questionnaire prepared by using 5 questions with demographic variables, academic ethical values scale and workplace deviation behavior scale were applied to 472 academicians working at state universities in Ankara and the nearby provinces. The results revealed moderately negative relationship between academic ethical values and one of its sub-dimensions which is the values for the institution and workplace deviation behaviors. Moreover, weak and strong negative relationships were found between academic ethical values and other sub-factors of workplace deviation behaviors. Intergenerational differences were found between academic ethical values and academic ethical values towards the teaching process and serious workplace deviation towards the organization, and between academic ethical values towards colleagues and deviant behaviors towards the organization.